Phenotypic shift of small intestinal intra‐epithelial type 1 innate lymphoid cells in celiac disease is associated with enhanced cytotoxic potential. (27th January 2020) - Uhde, M.; Yu, X.; Bunin, A.; Brauner, C.; Lewis, S. K.; Lebwohl, B.; Krishnareddy, S.; Alaedini, A.; Reizis, B.; Ghosh, S.; Green, P. H.; Bhagat, G.
Summary: The small intestinal (SI) epithelium harbors a heterogeneous population of lymphocytes that mediate mucosal damage and repair in celiac disease (CD). The composition and roles of human proximal SI intra‐epithelial innate lymphoid cells (ILCs), and their alterations in CD, are not well understood. We report that duodenal intra‐epithelial ILCs predominantly consist of natural killer (NK)p44 + CD127 − cytotoxic ILC1s and NKp44 − CD127 + helper ILC1s, while ILC3s only represent a minor population. In patients with newly diagnosed or active CD (ACD) and refractory CD type 1 (RCD I), the frequency of SI NKp44 + ILCs is decreased, with restoration of NKp44 + ILC frequency observed in patients adhering to a gluten‐free diet who show evidence of mucosal healing. Moreover, the frequency of SI NKp44 − ILCs is increased in ACD and RCD I patients and correlates with the severity of villous atrophy and epithelial damage, as assessed by serum levels of fatty acid binding protein 2 (FABP2). We show that the ILC alterations in CD represent a phenotypic shift of cytotoxic ILC1s rather than an increase in helper ILC1s or transdifferentiation of ILC1s to ILC3s, and activation‐induced loss of NKp44 by cytotoxic ILC1s is associated with increased interferon (IFN)‐γ expression and release of lytic granules. These findings suggest that intra‐epithelial NKp44 − CD127 − cytotoxic ILC1s may contribute to mucosal damage in CD. Abstract : In this study, we show that duodenal intraepithelial ILCs predominantly consist of NKp44 + CD127 − cytotoxic ILC1s (ieILC1s) and NKp44 − CD127 + helper ILC1s, while CD127 + ILC3s only represent a minor population. In celiac disease (CD), cytotoxic ILC1s undergo a phenotypic transition (downregulate NKp44 expression) and upregulate IFN‐γ. This phenomenon is mirrored in vitro upon activation of cytotoxic ILC1s and is associated with increased intracellular IFN‐γ and granzyme‐B expression and lytic granule release. These findings suggest that intraepithelial NKp44 − CD127 − cytotoxic ILC1s may foster intestinal inflammation and contribute to enterocyte damage in CD.